2013
DOI: 10.4236/ojmi.2013.32009
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Dental Indentation and Maxillary Sinusitis

Abstract: Purpose: To determine the relationship between the dental root indentation and maxillary sinusitis. Methods: We assessed the records of the patients who underwent paranasal sinus computed tomography imaging for suspected sinusitis. Results: We identified a total of 52 patients with a pre-diagnosis of maxillary sinusitis. Dental indentation was detected in 58 of 104 (55.7%) sinuses. Forty six of 58 sinuses (79.3%) with dental indentation had mucosal thickening higher than 2 mm. The difference between the groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…It is important to note that through vigorous exercise, the body burns fat and increases muscle and water percentage, leading to a decrease in ECW/ICW ratio and an increase in phase angle [15], as also proven by the presented studies. As muscles are mostly comprised of water (78%), an increase in muscle mass leads to an increase in the water ratio and thus reduces the fat ratio in the body [24]. The ECW/ICW ratio is closely tied to the phase angle value (in a reverse relation).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that through vigorous exercise, the body burns fat and increases muscle and water percentage, leading to a decrease in ECW/ICW ratio and an increase in phase angle [15], as also proven by the presented studies. As muscles are mostly comprised of water (78%), an increase in muscle mass leads to an increase in the water ratio and thus reduces the fat ratio in the body [24]. The ECW/ICW ratio is closely tied to the phase angle value (in a reverse relation).…”
Section: Discussionmentioning
confidence: 99%
“…This close proximity explains how the infectious process can easily extend from the abovementioned teeth to the maxillary sinus, where it is assumed that the tip of the root of the tooth will project toward the sinus floor causing minimal elevation and breakdown of the Schneiderian membrane, irritation and thickening of the sinus mucosa. 4,9,10 Radiological examination is a useful diagnostic tool in establishing the diagnosis of odontogenic sinusitis. 1,2,11 Standard radiological examinations include periapical and panoramic x-rays.…”
Section: Discussionmentioning
confidence: 99%
“…2,5 CT scan is the gold standard that can provide an assessment of the relationship of periapical lesions to the maxillary sinus floor and sinus soft tissue changes. 2,5,10 Research conducted by Little et al 2 in 2018 found that more than 70% findings of unilateral maxillary sinusitis suggest odontogenic infection. However, Patel et al 5 obtained only about 30% of radiological reports identifying an odontogenic source.…”
Section: Discussionmentioning
confidence: 99%
“…For 10–12% of cases of maxillary sinusitis, odontogenic factors are responsible [ 4 ]. Odontogenic pathologies such as apical inflammatory lesions, endodontic problems, radicular cysts, and marginal periodontitis can cause odontogenic sinusitis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%